Effectiveness of Quizizz in Enhancing Cognitive Competence in Mathematics at Islamic Elementary Schools - Khoiruddin, M Arif; Rahmawati, Elya (Noumerico: Journal of Technology in Mathematics Education, 2025)
This study investigates the effectiveness of Quizizz as a gamified learning platform in enhancing students’ cognitive competence in mathematics at an Islamic elementary school (Madrasah Ibtidaiyah). The study focuses on cognitive development, an area that is often underexplored in primary Islamic education. A quasi-experimental one-group pretest-posttest design was used, involving 20 fifth-grade students at MI Tarbiyatul Khoiriyah Kediri. Cognitive achievement was measured using a test aligned with Bloom’s revised taxonomy. The findings revealed a significant improvement in students’ cognitive competence, especially at the applying and analyzing levels. Quizizz supported active learning by engaging students in interactive, feedback-rich activities. Despite these positive outcomes, the study is limited by its small sample size, single-school setting, and short intervention period. Future research should include control groups and a larger population to validate and extend these results. Practically, the findings suggest that Quizizz can be systematically integrated into mathematics instruction at the Islamic elementary level to support structured cognitive development in an engaging and student-centered way.